2016
DOI: 10.1093/scan/nsw106
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin enhances inter-brain synchrony during social coordination in male adults

Abstract: Recent brain imaging research has revealed oxytocin (OT) effects on an individual's brain activity during social interaction but tells little about whether and how OT modulates the coherence of inter-brain activity related to two individuals' coordination behavior. We developed a new real-time coordination game that required two individuals of a dyad to synchronize with a partner (coordination task) or with a computer (control task) by counting in mind rhythmically. Electroencephalography (EEG) was recorded si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
120
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(134 citation statements)
references
References 72 publications
7
120
1
6
Order By: Relevance
“…A subsample of 80 participants (40 dyads) took part in the team neurosynchrony portion of the study. Prior EEG hyperscanning studies have employed anywhere from 12 participants (Dikker et al, in a group neurosynchrony study) to 68 participants (Mu et al, in a dyadic neurosynchrony study). Neurosynchrony study participants were all right‐handed, and reported no history of brain trauma and current prescriptions for medications that affect mental activity.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A subsample of 80 participants (40 dyads) took part in the team neurosynchrony portion of the study. Prior EEG hyperscanning studies have employed anywhere from 12 participants (Dikker et al, in a group neurosynchrony study) to 68 participants (Mu et al, in a dyadic neurosynchrony study). Neurosynchrony study participants were all right‐handed, and reported no history of brain trauma and current prescriptions for medications that affect mental activity.…”
Section: Methodsmentioning
confidence: 99%
“…Team neurosynchrony was assessed by calculating phase synchrony of continuous alpha‐band activity in the participants' EEG using PLV, an established measure of across‐brain neurosynchrony (Dumas et al, ; Linkenkaer‐Hansen, Nikouline, Palva, & Ilmoniemi, ; Mu et al, ). First, we identified time windows when both participants in each dyad were silent between conversations and computer usage.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations